Mantle plume tomography - Nolet, G.; Allen, R.; Zhao, D. (Chemical Geology, 2007)
Chemical Geology, v. 241, n. 3-4, p. 248-263, 2007. http://dx.doi.org/10.1016/j.chemgeo.2007.01.022 International audience We review the resolution currently available with seismic tomography, in particular the ability of seismic waves to image mantle plumes, and discuss frequently asked questions about artifacts, interpretation and possible systematic errors. These aspects are discussed in more detail for two case histories offering different problems in the tomographic interpretation: Iceland and Hawaii. Regional and global models resolve a vertical low velocity anomaly beneath Iceland, interpreted as an upwelling, from the transition zone up to the base of the lithosphere. Beneath the transition zone any continuation of the low-velocity anomaly is weak at best. This may be due to the absence of such an anomaly, poor seismic resolution in the lower mantle, or the weak sensitivity of velocity to buoyancy at these depths. While we are confident of the presence of a plume in the upper mantle, its origins remain to be resolved. Because of its large distance to most seismic sources and stations, the mantle structure under Hawaii is among the most difficult to image tomographically, but several recent global tomography studies agree on a whole-mantle plume under the Hawaiian hotspot. The plume exhibits a tilting geometry, which is likely due to the mantle flow. Theoretical advances, as well as deployments of large seismic networks across hotspot regions, are expected to bring significant improvements to the imaging of narrow mantle upwellings in the near future.